Nickel/Photoredox-Catalyzed Decarboxylative Coupling of Aryl Bromides with N-Protected Glycine as an Aminomethyl Source - Jung, Jaehyun; Kinoshita, Takumi; Makihara, Yuta; Sakakibara, Yota; Amaike, Kazuma; Murakami, Kei; Itami, Kenichiro (Synlett, 2023)
Benzylamines are important scaffolds that are ubiquitously found in various bioactive molecules. Among the benzylamine derivatives, primary benzylamines (ArCH2NH2) are regarded as valuable building blocks for pharmaceuticals. Herein, we report decarboxylative aminomethylation of aryl bromides with N-protected glycine under nickel/photoredox-catalyzed conditions. The corresponding products can be easily deprotected under acidic conditions to give primary benzylamines.
Keywords: benzylamines; aryl bromides; glycine; decarboxylation; aminomethylation; cross-coupling